2013
DOI: 10.5194/hess-17-3853-2013
|View full text |Cite
|
Sign up to set email alerts
|

The potential of radar-based ensemble forecasts for flash-flood early warning in the southern Swiss Alps

Abstract: Abstract. This study explores the limits of radar-based forecasting for hydrological runoff prediction. Two novel radarbased ensemble forecasting chains for flash-flood early warning are investigated in three catchments in the southern Swiss Alps and set in relation to deterministic discharge forecasts for the same catchments. The first radar-based ensemble forecasting chain is driven by NORA (Nowcasting of Orographic Rainfall by means of Analogues), an analogue-based heuristic nowcasting system to predict oro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 51 publications
4
68
0
Order By: Relevance
“…A modeling study by Paschalis et al (2014) showed that soil saturation can play a paramount role in mediating the discharge response of a small Pre-Alpine catchment. The initial conditions also significantly affect flash flood forecasting in the Southern Swiss Alps (Liechti et al, 2013). However, Norbiato et al (2009) found that the impact of initial moisture conditions on the runoff coefficient during floods is important only for catchments with intermediate subsurface water storage capacity; i.e., the role of initial moisture conditions is negligible for catchments with either very large or very small storage capacity.…”
Section: P Froidevaux Et Al: Flood-triggering Precipitation In Switmentioning
confidence: 99%
“…A modeling study by Paschalis et al (2014) showed that soil saturation can play a paramount role in mediating the discharge response of a small Pre-Alpine catchment. The initial conditions also significantly affect flash flood forecasting in the Southern Swiss Alps (Liechti et al, 2013). However, Norbiato et al (2009) found that the impact of initial moisture conditions on the runoff coefficient during floods is important only for catchments with intermediate subsurface water storage capacity; i.e., the role of initial moisture conditions is negligible for catchments with either very large or very small storage capacity.…”
Section: P Froidevaux Et Al: Flood-triggering Precipitation In Switmentioning
confidence: 99%
“…Scherrer, 1997). The third mapping approach we used is based on the experimentalist approach introduced by Schmocker-Fackel et al (2007) and Margreth et al (2010), which has already been used in, for instance, Antonetti et al (2016Antonetti et al ( , 2017. Basically, the approach consists of the following steps.…”
Section: Study Area and Process Mapsmentioning
confidence: 99%
“…The initial conditions can significantly affect simulation results, especially in a forecasting context (Liechti et al, 2013). For example, in a study about the uncertainties involved in operational flood forecasting chains in an alpine Swiss catchment, Zappa et al (2011) found that uncertainty in initial conditions lasts for the first 48 h, but is almost negligible compared with the uncertainty originating from meteorological data.…”
Section: Model Initialisationmentioning
confidence: 99%
“…Fast responding catchments are most prone to flash floods [7]. As pointed out by [8], accurate knowledge of the spatial and temporal distribution of rainfall is essential for flash flood early warning systems. The spatial scale should not exceed that of the catchments of interest or the typical convective storm within the area of interest.…”
Section: Introductionmentioning
confidence: 99%